1978
DOI: 10.1111/j.2042-7158.1978.tb13179.x
|View full text |Cite
|
Sign up to set email alerts
|

The stability of noradrenaline in physiological saline solutions

Abstract: Although noradrenaline is known to be stable for at least 4 h at room temperature in sterile solutions for intravenous infusion (Haggendal & Johnsson, 1967), it is well appreciated that noradrenaline is highly susceptible to chemical degradation by oxidation especially under the conditions found in isolated tissue baths (physiological saline, pH 7.4,37", oxygenation). For this reason many workers include stabilizing agents (typically ethylenediaminetetraacetic acid (EDTA) or ascorbic acid) in the physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 3 publications
2
31
0
Order By: Relevance
“…These results are in general agreement with all previously published studies, [5][6][7][8][9][10][11][12][13][14] which have all demonstrated the stability of norepinephrine. Of the papers published in English and reporting results obtained with stability-indicating analytical methods, 7,10-14 the study duration was relatively short, at only 24 h, 10,12,13 36 h, 7 or 7 days.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in general agreement with all previously published studies, [5][6][7][8][9][10][11][12][13][14] which have all demonstrated the stability of norepinephrine. Of the papers published in English and reporting results obtained with stability-indicating analytical methods, 7,10-14 the study duration was relatively short, at only 24 h, 10,12,13 36 h, 7 or 7 days.…”
Section: Discussionsupporting
confidence: 83%
“…Several investigators have evaluated the stability of norepinephrine in solutions intended for IV administration. [5][6][7][8][9][10][11][12][13][14] The concentrations evaluated were generally 16 mg/L or lower, although Allwood 11 and Peddicord and others 13 evaluated concentrations of 40 mg/L and 64 mg/L, respectively. Most of these studies reported the percentage remaining after only 24 h, and none evaluated the effect of light.…”
Section: Introductionmentioning
confidence: 99%
“…Following baseline, 1 M norepinephrine ϩ 1 mg/ml L-ascorbate (preservative) (20) were added to the perfusate through all fibers for 4 min to test vascular responsiveness and the integrity of Y ϩ P adrenoceptor antagonism. After a washout period (ϳ30 min) to allow CVC to recover to pre-norepinephrine baseline values, all sites were cooled at a rate of 3°/min, and Tloc was clamped at 24°C for 40 min, after which sites were rewarmed back to 34°C.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies, on which these recommendations are based, were conducted before the emergence of modern, precise, assay techniques such as high-performance liquid chromatography (HPLC). [2][3][4] The few studies performed, using modern measurement technology, reported the stability of NE in dextrose (5%) in water (D5W) at room temperature for a period up to 48 hr. [5][6][7][8] Stability of NE solutions for longer periods has not been studied.…”
Section: Ment Stables Pour Sept Jours Si Elles Sont Conservées à Tempmentioning
confidence: 99%